METASTATIC TUMORS OF THE ADRENAL GLAND: THE EXPERIENCE OF OUR CLINIC (World Bulletin of Public Health, 2024)
Differential diagnosis between benign, primary and secondary malignant tumors is a critical issue in the clinical management of adrenal tumors, especially in patients with isolated adrenal lesions. In most cases, the correct diagnosis can be established microscopically with standard hematoxylin and eosin staining. However, in some cases, it is almost impossible to differentiate metastasis from primary adrenal cancer, so immunohistochemistry is required to establish the diagnosis